2021
DOI: 10.1155/2021/7008898
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between BMP2/9 Levels and Spinal Function and Quality of Life in Patients with Severe Scoliosis after PVCR

Abstract: Objective. To explore the relationship between (bone fusion associated protein) bone morphogenetic protein (BMP)2 and BMP9 and spinal function and quality of life in patients with severe scoliosis after posterior vertebral column resection (PVCR). Methods. 78 cases of severe scoliosis treated with PVCR surgery in our hospital from January 2015 to April 2018 were selected and set as the observation group, and 80 health examiners in the same period were selected and set as the control group. The ELISA method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%